Analyzing Athlete-Family: A Bibliometric Study (2014–2024) - Seno Aji Wicaksono; Herman Subarjah; Wildan Akbar Firdaus; Dilal Hamdi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study analyzes trends, patterns, and contributions of research on the relationship between athletes and their families using bibliometric analysis based on Scopus data from 2014–2024. Through VOSviewer software, it maps keywords, author collaboration networks, and the geographical distribution of publications, identifying the United States as the most productive and influential country in this field. Key themes include family support, mental health, and athlete motivation. The analysis reveals growing interest in this area, with fluctuating but overall increasing publications, peaking in 2023. A notable contribution is the article "2015 ESC Guidelines for the Management of Patients with Ventricular Arrhythmias" by Priori et al., with 654 citations. Despite limitations such as language bias and reliance solely on Scopus sources, this study provides a valuable foundation for further research on the impact of family on athlete performance and well-being, offering opportunities to develop family-support-based interventions to optimize athlete potential.